Gut microbiota axis: potential target of phytochemicals from plant-based foods - Ruyu Shi; Congying Huang; Yuan Gao; Xing Li; Chunhong Zhang; Minhui Li (Food Science and Human Wellness)
Food-microbiota-host interactions provide an overarching framework for understanding the function of the gut microbiota axis. Diet is a major modulator of gut microbiota. Plant-based foods are rich in phytochemicals; therefore, it is essential to assess such foods and elucidate the mechanisms underlying their action. In this review, we summarize the role of gut microbiota in the communication between the gut and the brain, liver, lung, kidney, and joints, as well as the role of the gut microbiota axis in diseases involving these organs. In addition, we assess the effects of phytochemicals from plant-based foods on the gut microbiota axis via different pathways.